Efficacy of Native Entomopathogenic Nematodes on the Larvae of Tomato Leafminer Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Çiğdem Gözel; İsmail Kasap; Uğur Gözel (Journal of Agricultural Sciences)
This study was conducted to determine the efficacy of native entomopathogenic nematodes (EPNs); Steinernema affine 46 (Bovien, 1937), S. feltiae 879 (Filipjev, 1934), S. carpocapsae 1133 (Weiser, 1955) and Heterorhabditis bacteriophora 1144 (Poinar, 1976) on the larvae of tomato leafminer Tuta absoluta (Meyrick). Bioassays were conducted in the laboratory at four different temperatures (10, 15, 20 and 25±1 oC) in the plates and 30 infective juveniles (IJs) were inoculated to a single T. absoluta larva for each nematode species. After nematode inoculation, larvae were checked on the 3rd, 5th, 7th days and mortalities were recorded. All nematode species used in the study showed the lowest efficacy on the 3rd control day at 10 oC and the highest efficacy on the 7th day at 25 oC. S. feltiae 879 was found as the most efficient species with the highest mortality (91.67%) among EPNs used in the study. The results proved that T. absoluta larvae are highly susceptible to EPNs and the control of the pest by EPNs on this stage is successful.